Use of Bone Bank Grafts in Revision Total Hip Arthroplasty: Patient Characteristics at a Referral Center - Thiago de Carvalho Gontijo; Luiz Octávio Pereira Xavier; Lucas Carneiro Morais; Gustavo Waldolato Silva; Janaíne Cunha Polese; Raquel Bandeira da Silva; Amanda Aparecida Oliveira Leopoldino (Medicina)
Background and Objectives: To characterize the epidemiological profile of patients undergoing revision total hip arthroplasty (THA) using bone allografts from a tissue bank, and to identify clinical and surgical factors associated with the selection of graft type in cases of severe periprosthetic bone loss. Materials and Methods: This observational, cross-sectional study involved a retrospective review of medical records from a specialized referral center, including revision THA procedures performed between 2013 and 2019. Data were collected on 36 variables covering demographic details (age, sex), surgical history of both hips, comorbidities, medication use, perioperative complications, hospitalization, surgical technique, and characteristics of the bone grafts used. Patients were grouped based on the type of allograft received—structured or morselized (impacted)—and comparative analyses were performed. Results: A total of 67 revision THA cases were evaluated, with a mean patient age of 63.2 years. Nearly half (47.8%) had no prior hip revision. The average number of previous procedures per patient was 1.73, and the mean interval from primary THA to revision was 178.4 months. Morselized bone allografts were used in 66.7% of cases, and structured allografts in 33.3%. Patients receiving structured grafts had undergone a significantly higher number of prior surgeries (p = 0.01) and had a longer duration since the initial THA (p = 0.04). Conclusions: These findings suggest that younger patients undergoing primary total hip arthroplasty may be at increased risk for complex revision procedures involving structured grafts later in life, underscoring the need for long-term monitoring and tailored surgical planning in this population.